2014
DOI: 10.9790/0853-131172428
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice of Breastfeeding in a Rural Community of Bankura District, West Bengal, India

Abstract: A community-based, cross-sectional

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
1
2
1
Order By: Relevance
“…This study found few health service-related factors such as types and mode of delivery associated with exclusive breastfeeding. However, women with caesarian delivery were less likely to practice EBF compared to those with vaginal delivery; similar results were found in previous studies 21,22 . Caesarian mothers required more time to recovery from cesarean illness (fatigue, low blood pressure, unable to practice breastfeeding) and difficulty in moving; reasons why families were likely to introduce formula milk and not exclusive breastfeeding 12 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This study found few health service-related factors such as types and mode of delivery associated with exclusive breastfeeding. However, women with caesarian delivery were less likely to practice EBF compared to those with vaginal delivery; similar results were found in previous studies 21,22 . Caesarian mothers required more time to recovery from cesarean illness (fatigue, low blood pressure, unable to practice breastfeeding) and difficulty in moving; reasons why families were likely to introduce formula milk and not exclusive breastfeeding 12 .…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, this study found that some sociodemographic factors such as being a housewife, literate, having a high income, and being a single family, were more likely to practice EBF. Previous studies conducted among Malaysian 20 and Indian mothers 21 reported that non-working/housewife mothers were more likely to have good EBF practices than employed mothers who had poor knowledge and attitude toward EBF practice, leading to less exclusive breastfeeding practices, as found among Nepali 22 and Bangladeshi 16 mothers. Housewives can easily participate in Government and NGO implemented programs on Infant and Young Feeding (IYCF) practices available in the community, which makes them more positive toward EBF practices.…”
Section: Discussionmentioning
confidence: 85%
“…role of breastfeeding in contraception, which is quite dismal for a developing country like India where contraception plays a big impact on population control. A study in West Bengal by Abhay C. Pal et al (2014) showed that 68% of mothers had knowledge regarding contraceptive effect of breast milk, which is much higher in comparison to our study, but most of the other studies in India have shown similar results as ours [1011]. This could be due to different education level of the participants.…”
Section: Discussioncontrasting
confidence: 59%
“…Age >25 years, parity two or more, an educational level of grade 12 or higher, and being a housewife all positively affect EBF and are statistically significant (p-value 0.05); however, family income has no influence and is statistically insignificant (p-value 0.05). According to studies on mothers in India and Malaysia, housewives and mothers who are not employed are more likely to practice EBF than their counterparts [20,21]. In the current study, 67% (n = 268) of mothers were unaware of the benefits of colostrum.…”
Section: Discussionmentioning
confidence: 51%